Makna Slametan Adheg Omah dalam Perspektif Hindu Etnik Jawa di Desa Sumberarum Kecamatan Wlingi, Blitar - Dewi Ratnawati; I Made Suparta (Pasupati, 2022)
Slametan munggah molo is part of a series of ritual slametan adheg omah carried out by the Javanese community. However, in modern times slametan is rarely found in people's lives in Java, people argue that times have advanced. The discussion in this study includes (1) the Slametan Adheg Omah Munggah Molo procession, (2) public understanding of Slametan Adheg Omah (3) changes that occur in the Slametan Adheg Omah tradition. The benefits of this research are expected to be useful as a science of tradition in a Javanese ritual, as well as add insight, especially for the community. The method used is a qualitative. The results of the research and discussion about the slametan munggah molo procession in the Sumberarum community is carried out in the morning or afternoon by enacting laws to neighbors and closest relatives. The materials and tools used during the slametan are offerings and ubo rampe, offerings and ubo rampe are offered to ancestors or sing mbahurekso earth known as Sang Hyang Ismoyo Jati. Slametan is carried out with the aim of asking for safety when carrying out an activity. In the process of building a house, it is also related to the teachings of Tri Hita Karana, because is a source of happiness for humans and the universe. Slametan munggah molo also experienced a shift caused by several factors, namely the influence of culture, customary holders, the mass media which is getting stronger in social life, and socio-economic life.